PDF Faktor-Faktor yang Mempengaruhi Rendahnya Minat Ibu Menggunakan Alat Kontrasepsi Dalam Rahim (AKDR) Di Klinik Bidan Horasmiani Damanik Kec. Medan Deli - Subroto, Edi; Situmeang, Ayu Lestari; Ningsih, Esti Mulia (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
One of the factors that can cause the low use of IUDs is the lack of interest in?EFA. Based on the cross test above, the majority of respondents who did not?use MKJP had a negative socio-cultural attitude towards using MKJP, namely31 respondents (75%). From the results of the chi square test with a confidencelevel of 95% (? = 0.05) the calculation results show a p value (0.001) < p value(0.05) meaning that Ha is accepted and Ho is rejected, thus social culture cancause low IUD users. Results 34 respondents obtained from husband’s support,namely husband’s support was mostly good support 24 people (68.6%) and at least 11 people (31.4%) lacked support. The results of the study showed thathe knowledge of the majority of mothers of reproductive age couples was inthe sufficient category, namely 33 people (34.0%) with the use of IntrauterineContraception (IUD) in the category of not using the IUD, namely 20 people(24.0%) and using the IUD, namely 3 people ( 3.2%). Based on the results of thechi square test with a significance value of 0.001 <0.05, then Ho is rejected andHa is accepted. In conclusion, there is a relationship between the knowledge ofmothers of reproductive age couples and the use of Intrauterine ContraceptionDevices (IUD)